Episode of Situated Learning to Enhance Student Engagement and Promote Deep Learning: Preliminary Results in a High School Classroom - Terrenghi, Ilaria; Diana, Barbara; Zurloni, Valentino; Rivoltella, Pier Cesare; Elia, Massimiliano; Castañer, Marta; Camerino, Oleguer; Anguera, M. Teresa (Frontiers in Psychology, 2019)
Teaching is now experiencing a new centrality due to the fast socio-cultural transformations, the vertical growth of digital media and, therefore, the new ways children and young people learn. New paradigms and teaching methodologies are emerging to meet the new educational needs; among them, the “Episodes of Situated Learning” approach (EAS in Italian) was chosen for this study. This approach broadly refers to the “Flipped Class” model, in which the lesson structure reverses the traditional teaching/learning cycle with a positive outcome on engagement and learning. The present study aims to explore whether the EAS teaching methodology, according to literature about the Flipped Class model, has a positive outcome on student engagement, focusing on its emotional, cognitive and behavioral components. In particular, we hypothesize that the EAS teaching methodology changes teachers’ behavior in classroom, increasing their movements and body expression during the lesson. Moreover, we expect higher levels of self-efficacy and positive emotions and lower levels of perceived anxiety in teachers, thus improving students’ level of engagement. The research was conducted in a secondary school, in Milan, and includes a classroom of sixteen students and three teachers. We chose a quasi-experimental nested design, a mixed-method approach that combines the qualitative and quantitative collection and analysis of data, in order to reach, as far as possible, a holistic, effective and exhaustive representation of the studied phenomenon. Pre-post measures, including video-recording, systematic observation and questionnaires, of both students and teachers were collected during the eight months of experimentation. This research project could foster positive outcomes for participants as well as the broader society, in which school dropout is increasing. Many authors positively associate low levels of students’ engagement to high rates of school dropout; for this reason, working on improving teaching methodologies and students’ engagement measurement, could be an effective way to enhance learning and opposing school dropout.